The relationship between attitudes, self- regulation, game immersion, and perceived stress on online gaming intentions and behaviors among Chinese college students - Xiaodan, Wang; Ma’rof, Aini Azeqa; Abdullah, Haslinda (HRMARS, 2024)
This study investigates the impact of attitudes toward online gaming, self-regulation, game immersion, and perceived stress on online gaming intentions and behaviors among Chinese college students. A quantitative research design was employed with a sample of 453 participants. Pearson correlation and multiple regression analyses were used to explore the relationships between these variables. The results showed that attitudes toward online gaming and game immersion were the strongest predictors of online gaming intentions and behaviors, followed by perceived stress and self-regulation. Positive attitudes and deep immersion in online games significantly increased gaming intentions, while self-regulation played a protective role in reducing excessive gaming. Perceived stress was also found to elevate gaming intentions as a coping mechanism. These findings suggest that addressing attitudes, managing stress, promoting responsible gaming, and enhancing self-regulation could help in fostering healthier gaming habits among students. Universities and policymakers should consider implementing interventions to mitigate excessive gaming by promoting self-regulation and stress management.